Sosiologi Lembaga Pendidikan: Negosiasi Identitas Siswa dari Keluarga Prasejahtera dalam Mencapai Mobilitas Sosial - Muh. Hanif; Lu’lu Abyadah (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This article is designed to examine the negotiation of identity among students from pre-prosperous families in achieving educational mobility at Madrasah Aliyah through the perspective of the sociology of educational institutions. The main focus is directed at the claim that students from pre-prosperous families negotiate their social identity through academic achievement, discipline, and support networks in order to achieve educational mobility. The field research was conducted at MAN 2 Banyumas, which empirically demonstrates social practices related to this issue. Primary data were collected through observation of academic achievement as a strategy to gain social recognition, interviews with guidance and counseling teachers and pre-prosperous students, as well as documentation of institutional policies and programs. The three dimensions of evidence examined are: (1) academic achievement as a strategy for students to obtain social recognition, (2) teacher support and scholarships that sustain educational continuity, and (3) students' social resilience in facing family economic constraints. Using a qualitative case study approach, this article demonstrates how social relations, institutional norms, educational authority, as well as students' and teachers' experiences shape everyday educational practices. The contribution of this article does not stop at case description, but also builds a theoretical argument about how educational institutions function as social arenas that produce trust, identity, discipline, solidarity, and social change. The research findings are expected to enrich discussions on the sociology of Islamic education in Indonesia and offer recommendations for strengthening the governance of educational institutions based on field data.